Stress and Marital Adjustment in Parents of Children with Cancer: The Moderating Role of Emotion Regulation - Boparai, Sameen (My University, 2023)
Caregivers of children with cancer report high levels of distress and family conflict. Previous research has found that greater life stressors during the first year post-diagnosis predicted lower marital adjustment between caregivers. However, caregivers’ emotion regulation (ER) skills may allow them to handle co-occurring stressors more adaptively, maintaining the quality of family relationships. The current study examines whether caregivers’ ER moderates the relation between various stressors (negative life events, treatment related events, life threat, treatment intensity, financial strain) and the trajectory of marital adjustment during the first year of cancer treatment. Primary caregivers (n = 159) completed twelve monthly questionnaires after their child’s diagnosis. Their ER was measured both through an interview (observed ER) and through resting respiratory sinus arrhythmia (RSA). RSA moderated the association between life threat and marital adjustment at month twelve, such that life threat was only significantly associated with lower marital adjustment among caregivers with low RSA. The associations between the other stressors and marital adjustment were not moderated by either ER measure. Life threat may be a uniquely salient stressor because it is a fundamental fear that caregivers have little control over. Caregivers with higher resting RSA may be better equipped to maintain marital adjustment when faced with life threat to their child, although further replication is needed.
Thesis (Master's)--University of Washington, 2022
Keywords: emotion regulation; family relationships; marital relationships; pediatric cancer; respiratory sinus arrythmia; stress; Clinical psychology; Psychology; Counseling psychology; Psychology